2021
DOI: 10.2174/1874434602115010254
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Views on the Use, Quality, and Satisfaction with Electronic Medical Record in the Outpatient Department at a Tertiary Hospital

Abstract: Background: Many nurses perceive that the Electronic Medical Record (EMR) reduces the workload, improves the quality of documentation, and improves safety and patient care. However, other nurses reported that the system and environment of healthcare might impede EMR documentation at the bedside. Objective: The study aimed to describe the nurses' views of the use, quality, and satisfaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, an investigation found that nurses in an outpatient department of a tertiary hospital were satisfied with EMR based on their use, quality, and satisfaction. Positive correlations were also found among the service, quality, and satisfaction domains of EMR [34]. Also, computerization is viewed by nurses as a means of error reduction.…”
Section: Perceived Usefulness (Pu) Of Emrmentioning
confidence: 81%
“…Nevertheless, an investigation found that nurses in an outpatient department of a tertiary hospital were satisfied with EMR based on their use, quality, and satisfaction. Positive correlations were also found among the service, quality, and satisfaction domains of EMR [34]. Also, computerization is viewed by nurses as a means of error reduction.…”
Section: Perceived Usefulness (Pu) Of Emrmentioning
confidence: 81%
“…18 Additionally, factors such as age, training, and certain barriers, such as lack of training, resistance to EHR adoption, and lack of technical support, can influence perceptions and intentions to use EHR. 19 Besides training factors, organizational factors, such as support from administrative departments, IT departments, communication, and organizational culture, can affect perceptions and usage of Electronic Medical Records (EMR) by doctors and nurses. 20 The implementation of Electronic Health Records (EHR) impacts the time spent by nurses on various types of care interventions.…”
Section: Discussionmentioning
confidence: 99%
“…According to an investigation, nurses in an outpatient department of a tertiary hospital were satisfied with EMRs based on their use, quality, and satisfaction with the system. Furthermore, there was a positive correlation between the service, quality, and satisfaction domains of the EMR [57]. Computerization is also viewed by nurses as a means of reducing errors.…”
Section: Characteristicsmentioning
confidence: 93%